Dual Effect of Neutrophils on pIgR/Secretory Component in Human Bronchial Epithelial Cells: Role of TGF-β. (8th July 2010) - Ratajczak, Céline; Guisset, Amélie; Detry, Bruno; Sibille, Yves; Pilette, Charles
Abstract : Neutrophils have a dual affect on epithelial pIgR/SC, the critical receptor for transcellular routing of mucosal IgA, but mechanisms of pIgR/SC upregulation remain elusive. Requirements of cytokine, redox, and signalling pathways for pIgR/SC production were assessed in human bronchial epithelial (Calu-3) cells cocultured with increasing numbers of blood neutrophils. Increased SC production was observed after incubation for 48 hrs with intermediate neutrophil numbers (1.25 to 2.5 × 10 6 ), was favoured by the elastase inhibitor SLPI, and correlated with increased TGF-β production. Exogenous TGF-β stimulated SC production with a maximal effect at 48 hrs and both TGF-β - and neutrophil-driven SC upregulation were dependent on redox balance and p38 MAP-kinase activation. This paper shows that activated neutrophils could upregulate epithelial pIgR/SC production through TGF-β -mediated activation of a redox-sensitive and p38 MAPK-dependent pathway. An imbalance between the two neutrophil-driven opposite mechanisms (SC upregulation and SC degradation) could lead to downregulation of pIgR/SC, as observed in severe COPD.